Zircon U–Pb geochronology and geochemistry of Devonian plagiogranites in the Kuerti area of southern Chinese Altay, northwest China: Petrogenesis and tectonic evolution of late Paleozoic ophiolites. (27th September 2017) - Shen, Xiao‐Ming; Zhang, Hai‐Xiang; Wang, Qiang; Saha, Abhishek; Ma, Lin
Abstract : This study presents zircon U–Pb geochronology with major, trace, rare earth element and Sr–Nd isotope geochemistry for plagiogranite dyke swarms occurring within the gabbro unit of the lower part of the Kuerti ophiolite in southern Chinese Altay, Northwest China. These intrusive plagiogranites cut across the metamorphic zone consisting of amphibolites that are related to hydrothermal alteration and shearing of gabbros. LA‐ICP‐MS zircon U–Pb dating of 2 plagiogranite samples yields approximately 390 Ma age of origin. They are geochemically characterized by relatively high SiO2 and Na2 O, low K2 O, TiO2, and Al2 O3 contents, with marked enrichment in light rare earth elements and depletion in Nb, Ta, and Ti. They have slightly higher initial 87 Sr/ 86 Sr ratios (0.7040 to 0.7049), lower εNd (t) values (+3.6 to +6.3), and higher Th contents (2.84–11.9 ppm) than those (0.7034 to 0.7048, +7.2 to +10.3, and 0.04 to 1.79) of closely associated amphibolites. Geological and geochemical attributes suggest that the plagiogranites were generated by the anatexis of hydrated and hydrothermally altered amphibolites and minor sediments from oceanic crust during shearing at low pressure (<0.1 GPa) and temperature (<850 °C) conditions in a suprasubduction zone setting. The ridge subduction at approximately 390 Ma caused the upwelling of the hot asthenosphere and triggered the spreading of the Kuerti back‐arc basin, followed by the formation of the plagiogranites in the Kuerti ophiolite.